Leishmania infantum Virulence Factor A2 Protein: Linear B-Cell Epitope Mapping and Identification of Three Main Linear B-Cell Epitopes in Vaccinated and Naturally Infected Dogs - Campos, Monique Paiva; Figueiredo, Fabiano Borges; Morgado, Fernanda Nazaré; Renzetti, Alinne Rangel dos Santos; de Souza, Sara Maria Marques; Pereira, Sandro Antônio; Rodrigues-Da-Silva, Rodrigo Nunes; Lima-Junior, Josué Da Costa; De Luca, Paula Mello (Frontiers in Immunology, 2018)
In Brazil, canine visceral leishmaniasis (CVL) is caused by Leishmania infantum, presenting a broad spectrum of clinical manifestations. Dogs are the main parasite reservoir in urban areas and canine cases precede human infection. Currently, A2 protein based Leish-Tec® vaccine is the only vaccine commercially available against CVL in Brazil. Considering that the main screening and confirmatory tests of canine infection are serological, it is possible that the antibody response elicited after vaccination interfere with diagnosis, leading to the inability to distinguish between vaccinated and infected animals. In order to identify the specific B-cell response induced after vaccination, A2 protein sequence was screened for main linear B-cell epitopes using in silico prediction (Bepipred) and immunological confirmation by ELISA. Three amino acid sequences were described as potential B-cell epitopes (PP16-SAEPHKAAVDV, SV11-PQSVGGPLSVGPQSVGP and VQ34-VGPLSVGPQSVGPLSVGPLSVGPQAVGPLSVGPQ). Specific IgG ELISAs were performed in sera of 12 immunized dogs living in non-endemic areas, followed for up to one year after immunization. The results were compared with those obtained in a group of 10 symptomatic and 10 asymptomatic CVL dogs. All predicted epitopes were confirmed as linear B-cell epitopes broadly recognized by sera from studied dogs. Total IgG ELISAs demonstrated distinct patterns of response between peptides in the immunized and CVL groups. VQ34 peptide was recognized by the majority of sera from vaccinated and symptomatic dogs, and increases after vaccination. PP16 induced low levels of specific IgG that increased one year after immunization. Interestingly, a low frequency of reactivity was found against SV11 in naturally infected dogs (symptomatic and asymptomatic), while 83.3% of vaccinated dogs presented positive responses one year after immunization. The two animals in the vaccinated group that did not respond to SV11 one year after immunization presented positive serology both 30 days and 6 months after immunization. In summary, we identified three main linear B-cell epitopes in A2 based vaccine. Moreover, the humoral response against SV11 presented marked differences between infected and Leish-Tec vaccinated dogs, and should be further investigated, in large trials, to confirm its potential as a serological marker able to distinguish between infected and vaccinated dogs.